Changing organizational culture : - Alvesson, Mats (Routledge, 2016)
Changing Organizational Culture encourages the development of a reflexive approach to organizational change, providing insights as to why it may be difficult to maintain momentum in change processes. Based around an illuminating case study of a cultural change programme, the book provides 15 lessons on the entire change journey; from analysis and design, to implementation and how organizational members should approach change projects. This enhanced edition considers the most recent studies on organizational change practice, with new examples from businesses and the public sector, and includes one empirical study which uses the authors’ own framework, enriching their practical recommendations. It also draws on the latest theoretical developments, including ideas of power and storytelling.